Optimization Framework For Allocation of Banking Funds Based on Business Risks: A Systematic Literature Review - Moch Panji Agung Saputra; Diah Chaerani; Sukono; Mazlynda Md Yusuf (The International Association of Engineers (IAENG), 2026)
Indexed by WOS/Scopus/ERA